The confidence gap : from fear to freedom - Harris, Russ, 1966- (Camberwell, Vic. : Portfolio, 2010)
This is a hands-on, self-help guide to gaining long-lasting confidence and overcoming fear, using mindfulness-based therapy. The author explains how many of us are playing the 'confidence game' using the wrong rules, and guides the reader through clear, simple exercises designed to help you manage difficult emotions such as anxiety, and build genuine confidence. The Confidence Gap has a gentler, more thoughtful approach to teaching confidence than the typically aggressive/peppy self-help approach. It is instructive, reassuring and gentle in tone, which will appeal to women as well as men and the business market.
Includes bibliographical references (p. 268-269) and index.
Keywords: Self-confidence.; Attitude (Psychology); Meditation -- Therapeutic use